Interaction and localisation: new insights into early metallurgy in China - Chen, K; Mei, J; Wang, L; Hein, AM (University of Hawaii Press, 2022)
The beginning and early development of metallurgy in China have long been hot topics in Eurasian archaeology since they were suggested to be closely linked with the so-called ‘prehistoric globalization’. This paper assesses the available archaeological and archaeometallurgical evidence within their temporal-spatial framework and explores diachronic and cross-spatial developmental processes of early metallurgy in different regions in China. While recognizing the importance of long-distance interaction and exogenous technological stimulation, we draw attention to the local adoption and adaptation process of metallurgy and highlight the significance of local communities as sponsors, practitioners, and consumers of the metallurgical products and production as well as agents of technology transmission. While previous research has focused on individual object features that were seen as typical for specific archaeological cultures, current data shows considerable similarities in artefact typologies and material types among the early metal-using societies throughout Northwest China. We therefore argue that the modification of foreign metallurgical traditions through localised practice in Northwest China was crucial for their transmission further eastward and thus for the ultimate establishment of a new metallurgical tradition in the Central Plain of China.